S14-3: Ensuring the Voices of Adolescents are Heard in the Planning, Implementation, and Evaluation of School-Based Physical Activity Interventions (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Public involvement in the design and conduct of research can improve research integrity, quality, and relevance. Despite growing calls for the involvement of young people in decision-making and the recognition of schools as an important setting for implementing physical activity interventions, conducting public involvement in this setting presents unique challenges and there is minimal knowledge on how public involvement is facilitated in studies involving children and young people due to sub-optimal reporting.This presentation will emphasise the importance of public involvement in research and outline examples from two studies conducted in Northern Ireland, the Walking In ScHools (WISH) study and the Youth-Physical Activity Towards Health in Northern Ireland (Y-PATH NI) study.Methods: Youth Advisory Groups (YAG) were set up across both studies to involve adolescents in the delivery, implementation, and dissemination of school-based physical activity (WISH) and physical education (Y-PATH NI) interventions targeted at adolescents. Across both studies, pupils aged 12–14 years were invited to attend YAG meetings, hosted by the research team. Participative methods were used to inform recruitment strategies, data collection methods, intervention materials, and dissemination.Results: Across the WISH study, pupils attended three YAG meetings (n = 51 pupils from n = 8 schools), while the Y-PATH NI intervention was informed by two YAG meetings (n = 38 pupils from n = 5 schools). Pupils reported enjoying the YAG meetings, felt that their feedback was valued, and considered the meetings a good way to get young people involved in research. The YAG advised on specific issues and informed several key decisions in both studies. There were many examples of the impact of involvement, including low attrition rates and high levels of pupil engagement with data collection.Conclusion: The case studies presented outline how public involvement can be conducted in the school setting. Based on our experiences to date, we plan to establish a Patient and Public Involvement panel in each participating school to further amplify the voice of adolescents in the planning, design, and conduct of school-based interventions, and ensure interventions are context-specific. These panels will advise on issues specific to their school environment, with the aim of enhancing implementation and adherence to the intervention.